2007
DOI: 10.1002/ijc.23210
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling to identify markers associated with deregulated hTERT in HPV‐transformed keratinocytes and cervical cancer

Abstract: Although high-risk human papillomavirus (HPV) infection plays a major role in the development of cervical cancer, additive oncogenic events are involved as well. One key event involves increased activity of telomerase resulting from a deregulated expression of its catalytic subunit hTERT. Our previous microcell-mediated chromosome transfer studies revealed that introduction of human chromosome 6 in the HPV16-immortalized keratinocyte cell line FK16A and in the HPV16-containing cervical cancer cell line SiHa in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…Gene alterations previously detected in our in vitro model system, such as GATA-3, hTERT, MGP and CADM1, were also found in clinical samples (Steenbergen et al, 2001(Steenbergen et al, , 2002(Steenbergen et al, , 2004de Wilde et al, 2007). Therefore, we believe that the methylation events identified in the in vitro model system provide potential markers for cervical cancer detection as well, which is underlined by their large overlap with methylated gene promoters found in cervical carcinomas.…”
Section: Discussionsupporting
confidence: 63%
“…Gene alterations previously detected in our in vitro model system, such as GATA-3, hTERT, MGP and CADM1, were also found in clinical samples (Steenbergen et al, 2001(Steenbergen et al, , 2002(Steenbergen et al, , 2004de Wilde et al, 2007). Therefore, we believe that the methylation events identified in the in vitro model system provide potential markers for cervical cancer detection as well, which is underlined by their large overlap with methylated gene promoters found in cervical carcinomas.…”
Section: Discussionsupporting
confidence: 63%
“…For hTERT mRNA expression analysis, 500 ng of total RNA was treated with RQ1 RNase-free DNase (Promega), and qRT-PCR was performed as described previously (35).…”
Section: Generation Of Retroviral Constructsmentioning
confidence: 99%
“…Infections with the hrHPV types 16,18,31,33,35,45,52, and 58 comprise the highest long-term (Ͼ5-year) risk of CIN3 or higher lesions, whereas most of the other hrHPV types present an almost negligible long-term risk (8)(9)(10). Furthermore, a large, randomized, controlled prospective trial conducted in the Netherlands has revealed that among hrHPV-positive women with normal cytology or borderline to moderate dyskaryosis, those infected with hrHPV types 16, 18, 31, and 33 have an increased 18-month risk of CIN3 or cancer (8).…”
mentioning
confidence: 99%
“…After statistical analysis, we were able to validate 28 upregulated and seven downregulated genes. Our findings represent a collection of cancer-related genes and a variety of genes associated with cell development and cell cycle mechanisms that have not been reported by other authors [8,[25][26][27][28].…”
Section: Discussionmentioning
confidence: 44%